Optimization model for assigning students to the residential halls in UUM - Abdul Razak, Nurul Syafiqah; Abdul Rahim, Mohd Kamarul Irwan (Universiti Utara Malaysia, 2020)
This research is about students enrolled to the residential halls at University Utara Malaysia (UUM). Each of the students are assigned to each residential hall by Students Accommodation Centre (SAC). In this study, we are focusing on 15 residential halls that UUM provided to all students. This research using quantitative methods for collecting of information through the questionnaires to choose which residential hall that students preferred to stay at UUM. This study involved 50 UUM students as the respondents. By applying mathematical programming, we are helping the administrators with the assignment process. As a result, we have established the accurate decision by using A Mathematical Programming Language (AMPL) software. The simple AMPL programming was used to solve the practical application by using some mathematical model to find an optimum solution. Moreover, this research aims to complete the residential hall placement of the students by the assignment problem by using mathematical programming method. The findings of the study will be used to increase knowledge on the issue of the appropriate residential hall placement for students.